Fermentation of soybean residue (Okara) : potential in food applications - Mok, Wai Kit (Nanyang Technological University, 2021)
With global population projected to reach 9.20 billion in 2050, food security is becoming an increasingly important issue. However, rapid industrialization and urbanization taxes heavily on the finite natural resources that we have. As such, traditional methods of enhancing food security will no longer be feasible due to resource constraints. Therefore, technologically advanced techniques have to be employed to enhance food security and, in these aspects, Singapore, with its little land space and natural resources is the perfect testbed and case study for our increasingly resource-scarce world. Singapore’s strategies for enhancing food security can be redefined to include 3 main areas: urban farming, processing technology and alternative food sources. This thesis would focus on the area of food waste processing technology. It aims to develop a strategy to enhance the nutrient profile of soybean residue (okara), thereby utilizing it as a food ingredient to enhance food security. The methodologies developed should also not generate secondary waste since food wastage has been found to contribute significantly to climate change, which can in turn affect food security. Solid-state fermentation, which is a low-cost microbial technique, was utilized to valorise okara using the bacterial strain Bacillus subtilis WX-17, which is a probiotic found in the human body. Results showed that after fermentation, valorisation was achieved. Total amino acids content increased from 3.04 ± 0.140 mg/g in unfermented okara to 5.41 ± 1.21 mg/g in fermented okara. Total fatty acids content increased from 153 ± 5.10 to 166 ± 2.41 mg/g okara after fermentation. 0.382 mg/100g of menaquinone-7 was also detected in fermented okara compared to almost nothing in unfermented okara. Total phenolic content and antioxidant content (DPPH) also increased by 4.09 and 6.40 times respectively. The findings of this work demonstrated the potential of using Bacillus subtilis WX-17 fermentation to enhance the nutritional profile of okara. This could serve as a potential low-cost food ingredient, which can be incorporated into the human diet. Following the successful valorisation of okara, an in vitro digestion and fermentation model was used to evaluate its potential effects in the human body. Bioaccessibility of nutrients, probiotic viability, cytotoxicity, total phenolic content, antioxidant activity as well as the microbial community of fermented and unfermented okara were evaluated. Fermented okara showed increased bioaccessibility of amino acids, fatty acids and menaquinone-7. Bacillus subtilis WX-17 also remained viable after in vitro digestion. Phenolic compounds and antioxidant activities were higher in fermented okara in both simulated small and large intestines. Production of SCFA was higher in the model using fermented okara. The gut microbiota was also found to be different between fermented and unfermented okara. These data suggest that the use of fermented okara as a potential functional, probiotic and prebiotic food ingredient is feasible. It would also confer more health benefits compared to unfermented okara. After proving the feasibility of using fermented okara as a food ingredient, an alternative method of fermentation was explored to expand its application as well as enhance the scalability of the process. Here, submerged liquid fermentation of okara by Bacillus subtilis WX-17 was used to produce a novel functional probiotic beverage. Metabolomics analysis showed that amino acids as well as short chain fatty acids were significantly (p<0.05) upregulated. Total phenolic content and antioxidant content (in terms of DPPH radical scavenging activity) increased by 6.32 and 1.55 times respectively. After 6 weeks, probiotic viability remained unchanged when stored at 4°C and the cell count is above the minimum dosage to confer health benefits. Antimicrobial activity was also detected against gram-positive bacteria. The findings of this work showed the potential of submerged liquid fermentation of Bacillus subtilis WX-17 using okara as sole substrate to produce a functional and low-cost probiotic beverage. The results achieved within this thesis successfully demonstrated low-cost methodologies to utilize fermented okara as food ingredients. Large-scale adoption of these strategies can potentially enhance the food security of Singapore. At the same time, the strategies proposed also do not generate secondary waste.